ОБРАЗОВАТЕЛЬНО-ВОСПИТАТЕЛЬНЫЕ ИДЕИ И МЫСЛИ В КАРАКАЛПАКСКИХ НАРОДНЫХ ЭПОСАХ (На примере эпоса «Шарьяр») - Абдуллаева, Р.А.; Толегенова, Г.Ж. (SCIENCE and SOCIETY, 2024)
The article examines didactic, educational, and ideological views of the Karakalpak folk epic. Through this epic, the ideas of kindness, justice, respect for people, and deep love for the child were deeply inculcated in the children. In the epic, negative characters with qualities such as hypocrisy, injustice, and cruelty, supporters of evil serve to form ideas against such vices of human nature in schoolchildren and young people.
Keywords: epic; didactic; character; idea; the first and second Renaissance; hypocrisy; cruelty; hard work; free thinking; moral education; spiritual forces